Beckman IR spectrophotometer power supply circuit diagram - Beckman Instruments, Inc. (1946)
The Beckman Instruments IR spectrophotometers began as a request from the Office of Rubber Reserve to Arnold O. Beckman in 1942, asking for an infrared spectrophotometer that they could use to create rubber. Under this contract, Beckman Instruments developed a single-beam spectrophotometer based on Robert Battrain’s extant design, which in 1942 was sold as the IR-1. With the IR-4 in 1956, Beckman Instruments branched out into double-beam design and kicked off a golden age of IR spectrophotometer production that lasted until 1973.
Keywords: Scientific apparatus and instruments; Spectrophotometer; Infrared spectroscopy; Blueprints; Beckman Instruments, Inc.